ADAPTATION OF LEARNING WORK MODEL VOCATIONAL EDUCATION VISUAL COMMUNICATION DESIGN FIELD OF STUDY (CASE STUDY) - A, Deden Maulana (CENTRAL ASIA AND THE CAUCASUS, 2022)
The model of implementing learning in vocational schools at the diploma tertiary level has provided a challenge and opportunity in developing attitudes, knowledge and creativity-based skills for students. The development of independence in students becomes the main part that has a very important position and role. The current learning model is no longer how participants can only study from an institution, but how students can have the space and opportunity to develop themselves, become human beings who dare to have the right attitude of human values. Having the habit of dealing with independent work patterns and ethos and being able to develop abilities that are in accordance with the expectations and desires of the future, which are more than what his mind thought during that time.Students can have the feasibility of compiling a pattern of study and work with the feasibility of a planned life with the ability to harmonize their hopes and ideals.The current and future student learning model is no longer just studying at an institution with all the limitations that cannot accelerate their thoughts and expectations. The learning model in higher education with a vocational level will be more appropriate for how students can study and work or work and study. These two words, Work Learning and Work Learning will encourage students to interact more, play an active role, open up and be able to position themselves as a more human student.The purpose of this modeling will give students a more pleasant sense of attitude, knowledge and skills in setting the real life education agenda. The role of educational institutions is only proper as a mover, motivating, directing, describing every desire of the students, not vice versa as an organizer of past education, only providing lessons. The modeling approach can be broadly translated by adapting the familiar approach model, namely; approach and apply the basic model of approach to problems (problem base learning), conduct independent and group discussions, as well as (focus group discussions) strong and understand in making presentation skills. While the results of the modeling of Work Learning – Work Learning, each student will develop faster as a more productive human being to give birth to new things according to his hopes and aspirations.